Effect of Yoganidra on Blood Pressure, Hs-CRP, and Lipid Profile of Hypertensive Subjects: A Pilot Study. (30th December 2021) - Devraj, J. P.; Santosh Kumar, B.; Raja Sriswan, M.; Jagdish, B.; Priya, B. S.; Neelu, S. B.; Desai Rao, Vijayabhaskar; Kumar, Manoj; Geddam, J. J. Babu; Hemalatha, R.
Abstract : Background . Yoganidra is a systematic method of promoting a state of complete physical, mental, and emotional relaxation. It is a safe, inexpensive, and very effective method of management of hypertension when used along with standard pharmacological therapy. This study aims to assess the effect of yoganidra on blood pressure (both systolic blood pressure (SBP) and diastolic blood pressure (DBP)), Hs-CRP, and lipid profile of hypertensive subjects at the time of enrollment (subjects that are hypertensive at the time of enrollment). Methods . Both treated and untreated subjects ( n = 74) with hypertension (blood pressure ≥140/90 mmHg) and age between 35 and 70 years were included in this study after obtaining ICMR-NIN-IEC approval and written informed consent from all subjects. Subjects with critical illness and/or psychological disturbances were excluded from this study. The subjects in the experimental group ( n = 31) practiced yoganidra for 45 minutes daily for 12 weeks under strict supervision. There was no intervention in the control group ( n = 43). Weekly blood pressure was recorded in the experimental group, whereas it was performed at baseline and at endpoint for control groups. Hs-CRP and lipid profile were estimated at baseline and endpoint for both the groups. Results . A significant reduction in mean SBP from 142.9 mm Hg (SD ± 16.46) to 118.68 mm Hg (SD ± 9.21; p value 0.0001) and DBP from 89.84 mm Hg (SD ± 10.42) to 77.03 mm Hg (SD ± 6.47: p value 0.0001) was observed among the experimental group after 12 weeks of yoganidra practice when compared with the control group. A significant reduction in mean Hs-CRP (2.21 ± 1.49 to 1.06 ± 0.82 mg/L, p < 0.001 ∗ ∗ ∗ ) was observed among the experimental group. There were no significant differences between triglycerides and total cholesterol levels, whereas LDL-C and HDL-C showed a trend of improvement in the experimental group after intervention. Conclusions . In this pilot study, we observed a significant reduction in blood pressure and Hs-CRP in the yoganidra group compared with the control group. There were no significant side effects observed in the intervention group during the study period.